FIBROMYALGIA: A SEARCH FOR MARKERS AND THEIR EVALUATION THROUGHOUT A TREATMENT - Jose Luis Pareja; Franz Martín; Genoveva Berná; Oscar Cáceres; Manuel Blanco; Francisco A Prada; Francisco José Berral (European Scientific Journal, ESJ, 2015)
Fibromyalgia syndrome (FM) is a complex chronic pain disorder of unknown causation associated with debilitating fatigue, unrefreshing sleep, cognitive and affective symptoms. There is no biological markers to monitor FM progression and no permanent cure for FM. Our aim was to identify markers associated with FM and its progression and to evaluate the efficacy of a battery of treatments. The study is a treatment trial, open label and single centre, with 27 women (41 ± 2 years) diagnosed with FM using the Widespread Pain Index (WPI), the Symptom Severity (SS) Scale and the Fibromyalgia Impact Questionnaire (FIQ). Anthropometric parameters, plasma cytokines values and clinical progression were measured before and after two months of a multi-approach treatment. A significant improvement was observed after two months of treatment as shown by WPI, SS Scale and FIQ. No significant variations were observed, except for the intracellular body water parameters, in anthropometric and body composition characteristics. Food-induced histaminosis release was observed to cow´s milk, egg, fruit, wheat and oily fish. Interleukin-1β (IL-1β) and interleukin-6 (IL-6) plasma cytokine values were significantly higher in FM. A strong positive correlation was observed between the percentage of reduction of cytokine levels and the improvement of health status. We propose: i) the existence of different subsets of FM patients; ii) the use of intracellular body water and plasma cytokine values as positive markers for FM progression; iii) that food-sensitisation could be an important mechanism for FM pathogenesis and iv) the use of a multidisciplinary approach for FM treatment.